Estimation of forage consumption for two dairy cattle biotypes in the high Andean tropics of Nariño, Colombia: Consumo materia seca bovinos - Cardona Iglesias, Juan Leonardo (2021)
The implementation of efficient grazing technologies in high mountain cattle ranches in the department of Nariño (Colombia) increases the sustainability of these production systems and promotes the conservation of the landscape design. With the objective of evaluating the dry matter intake of F1 (Kiwi-cross x Holstein) and Holstein cattle biotypes, present in hillside areas of the Nariño mountain, a preliminary trial of individual consumption of ryegrass (Lolium perenne) was carried out in Pasto (Nariño-Colombia) with the gauging technique, and the results were compared with models reported in the literature. The data were analyzed as a completely randomized design, with repeated measures over time. Intake per gauging was higher (p<0.05) in Holstein cows, with respect to F1 cows (12.74 vs. 9.69 kg/dry-matter/day), but per unit live weight was similar (p>0.05). On the other hand, the milk composition of F1 cows was superior (p<0.05) for fat, protein, and total solids (%). In conclusion, the two breeds evaluated recorded the same forage intake capacity as a function of live weight, but, due to the larger size of the Holstein cows the absolute intake was higher, indicating that an adjustment in forage supply should be made according to the size of the animals. This work contributes to improve grazing techniques, making the use of pastures and their environment more sustainable, which favors productive efficiency and improves the quality of life for the producer families in the area.